2020
DOI: 10.30935/conmaths/9288
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Male and Female Distance Learners’ Mathematics Achievement

Abstract: The purpose of this Ex Post facto study was to investigate the difference in mathematics achievement between male and female learners offering Diploma in Basic Education (DBE) by distance at the Institute for Distance and e-Learning (IDeL), University of Education, Winneba (UEW). Three consecutive year cohort groups (i.e. 2015, 2016 and 2017) of DBE distance learners were purposively selected from all the forty distance education centers of IDeL-UEW. There were 6,468, 3,483 and 3,276 learners in the 2015, 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Neither category of students could outperform the other. This revelation confirms scores of work done by some researchers who had similar results (Ajai & Imoko, 2015;Alkhateeb, 2001;Armah et al, 2020)…”
Section: Discussionsupporting
confidence: 88%
“…Neither category of students could outperform the other. This revelation confirms scores of work done by some researchers who had similar results (Ajai & Imoko, 2015;Alkhateeb, 2001;Armah et al, 2020)…”
Section: Discussionsupporting
confidence: 88%
“…The above findings also confirmed the research study carried out in Spain by Rodriguez et al (2020) on gender differences in mathematics motivation and its differential effects on performance in education; which pointed out that comparing female learners with boys, females lack the zeal, always demonstrate weak performance, thought that mathematics is only meant for males; and were anxious about mathematics. Research conducted by Armah et al (2021) in Ghana on sex differences in mathematics achievement among male and female distance learners revealed that both male and female learners' performance in mathematics were below average grades. I.e., D+, D and E. However, the performance of male distance learners outweighed their female counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the less responsible students are expected to be more significantly impacted by the new educational structures. According to Armah et al (2020), Lau et al (2018), Los andSchweinle (2019), andvan Putten et al (2020), female students are often more responsible than their male peers in learning mathematics; this can explain why male students are experiencing an even higher decrease in their mathematics achievement than their female counterparts.…”
Section: Discussionmentioning
confidence: 99%